The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5110/jjseg.50.238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Fractures as the Major Water-conducting Features in Neogene Sedimentary Rocks

Abstract: Ke ywo r d s :新第三紀堆積岩 n e o g e n es e d i me n t a r yr o c k s , 割れ目の開口性 f r a c t u r ea p e r t u r e , 割れ目の連続性・ 連結性 f r a c t u r ei n t e r c o n n e c t i v i t y , 水みち wa t e r c o n d u c t i n gf e a t u r e * (独) 日本原子力研究開発機構地層処分研究開発部門 J a p a n At o mi cEn e r g yAg e n c y , Ge o l o g i c a l I s o l a t i o nRe s e a r c ha n dDe v e l o p me n tDi r e c t o r a t e (会員) m,2 7 2 . 6 ~2 7 4 . 6 m,2 8 7 . 1 ~2 8 9 . 1 m,3 2 0 . 9 ~3 2 2 . 9 m,3 6 2 . 2 ~3 6 4 . 2 m,3 9 7 . 7 ~3 9 9 . 7 mでは,F P に剪断… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The chronology of fault formation can be estimated from their orientations. The most common orientations of faults are the same in both the Wakkanai and Koetoi formations, nearly perpendicular to bedding planes in the Wakkanai Formation [ Funaki et al , 2009]. Because bedding planes have different orientations from borehole to borehole, they were rotated into the horizontal plane to enable an analysis of the fault orientations.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chronology of fault formation can be estimated from their orientations. The most common orientations of faults are the same in both the Wakkanai and Koetoi formations, nearly perpendicular to bedding planes in the Wakkanai Formation [ Funaki et al , 2009]. Because bedding planes have different orientations from borehole to borehole, they were rotated into the horizontal plane to enable an analysis of the fault orientations.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Previous studies, using geophysical and fluid logging techniques, and in situ hydraulic tests, showed that the Koetoi Formation is a hydrogeologically porous medium because of its poor connectivity and the closing of fractures, while the Wakkanai Formation has, in part, the hydrogeological properties of a fractured medium, because of moderate connectivity and the opening of fractures [ Kurikami et al , 2008; Funaki et al , 2009]. In this study, mudstones having a log K i‐packer / K i‐lab <3 are assumed to behave hydrogeologically as porous media, while those with a log K i‐packer / K i‐lab >3 are assumed to have the hydrogeological properties of fractured media.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractures in the Koetoi Formation consist of many faults and few tension fractures [19]. The fault length is generally about 1 m [20] (Fig.…”
Section: Fault-slip Analysismentioning
confidence: 99%